Homeopathic Management of Planter Dermatosis and Recurrent URTI Evidence based Case Report - Raut, Ragini M.; M. Shaikh, Nilofer; Nadgauda, Sameer S. (Journal of Neonatal Surgery, 2025)
Background: Dermatitis of the palms and soles is a skin condition characterized by inflammation, redness, scaling, and sometimes itching or pain in these areas. It can manifest in various forms, such as dyshidrotic dermatitis, hyperkeratotic palmar dermatitis, or contact dermatitis. Dyshidrotic dermatitis often presents as small, itchy blisters on the palms and soles, which may rupture and cause crusting. Hyperkeratotic palmar dermatitis, on the other hand, is marked by thickened, scaly skin and painful fissures, primarily on the palms. Contact dermatitis can result from exposure to irritants or allergens, leading to localized inflammation. Factors like frequent handwashing, exposure to harsh chemicals, or underlying conditions such as atopic dermatitis can contribute to the development of this condition. Treatment typically involves identifying and avoiding triggers, using topical corticosteroids or emollients, and in severe cases, systemic medications or phototherapy. Early diagnosis and management are essential to prevent complications and improve quality of life Methods: Homeopathic medicine selected by prescription based on mind symptoms and gestures alone, in low potency, single medicine and infrequent repetition, can be implemented with good results. Pulsatilla in 30 potency single dose stimulation can be implemented on symptom similarity. Result: In planter dermatosis and recurrent URTI patient after3 doses of homeopathic medicine Pulsatilla in 30 potency at every 10 minutes time interval as a first stimulation, in next 15 days follow up patient was comfortable, with next few follow ups case recovered. Conclusion: Accuracy in homeopathic prescription by concept of individuals' mental state and gestures used to express their feelings in the illness yields good clinical results in case of planter dermatosis and recurrent URTI. After treatment with homeopathic medicine, clinical and evidence based results can be achieved.